‘This Is a Country To Earn and Return’: Polish Migrants’ Circular Migration to Iceland - Dziekońska, Małgorzata (Nordic Journal of Migration Research, 2021)
The problem under investigation in this article is circular migration of Polish men working in Iceland and its consequences for migrants’ lives, as well as the lives of those who stay. The phenomenon is discussed on the basis of the research conducted among migrants and complemented by their wives’ perspectives. The research was designed in two parts: one was conducted in Iceland with the migrants, and the other was conducted in Poland with their wives. The basic findings show how migrants physically and emotionally adapt to living in two locations and how they manage to settle in constantly changing schedules. The implications of the study are that, aside from financial stability, circular labour migration of male family members introduces rhythm, predictability, and a special set of rituals into the family life. All these become the household norm.